2018
DOI: 10.3389/fneur.2018.00081
|View full text |Cite
|
Sign up to set email alerts
|

Management of Refractory Orofacial Dyskinesia Caused by Anti-N-methyl-d-aspartate Receptor Encephalitis Using Botulinum Toxin

Abstract: The use of botulinum neurotoxin serotype A (BoNT-A) injections for the treatment of orofacial dyskinesia secondary to anti-N-methyl-d-aspartate receptor (NMDAR) encephalitis is rarely reported. Here, we report a case of an urgent, successful management of severe orofacial dyskinesia in an 8-year-old girl with anti-NMDAR encephalitis using BoNT-A injection. The patient presented with de novo unilateral paroxysmal movement disorder progressing to generalized dystonia and repetitive orofacial dyskinesia. Diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Previous studies have reported OFLD as a possible indicator of illness progression, which may assist in clinical assessment and treatment planning (Duan et al., 2016 ; Epstein & Difazio, 2007 ; Morales‐Briceño & Fung, 2017 ; Zheng et al., 2018 ). Moreover, current literature suggests that co‐morbid MDs are more common in biologically female individuals diagnosed with anti‐NMDAR encephalitis (Varley et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported OFLD as a possible indicator of illness progression, which may assist in clinical assessment and treatment planning (Duan et al., 2016 ; Epstein & Difazio, 2007 ; Morales‐Briceño & Fung, 2017 ; Zheng et al., 2018 ). Moreover, current literature suggests that co‐morbid MDs are more common in biologically female individuals diagnosed with anti‐NMDAR encephalitis (Varley et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…While orofacial dyskinesia, as a type of involuntary movement, is commonly seen as an extrapyramidal side effect of antipsychotics ( 18 ), patients with Huntington's disease, chronic hepatic encephalopathy, or infectious or paraneoplastic encephalitis can also show these abnormal movements ( 19 ). Oral involuntary movements are also observed in some forms of limbic encephalitis, although no definitive conclusions have been reached regarding the underlying mechanisms ( 20 , 21 ). The present case had no clinical history involving drug use or diseases that could cause dyskinesia.…”
Section: Discussionmentioning
confidence: 99%
“…Re‐emergence of the dystonic tremor within 5 months despite a partial resolution in MRI and no new lesion indicated that the earlier improvement occurred as a result of the botulinum toxin. Prior to this, botulinum toxin has been documented to be used once for anti‐NMDARE MDs 8 . In this case, botulinum toxin was administered early on in the treatment regime to optimize the young patient's functionality and quality of life 9 .…”
Section: Discussionmentioning
confidence: 99%